(untitled) (Journal of Philosophy, Culture and Political Science, 2025)
Following the February 2023 earthquake in southeastern Türkiye, South Korea provided comprehensive disaster relief. This study examines whether Hallyu (Korean Wave) amplified South Korea’s disaster support in the context of public diplomacy by influencing foreign publics. As South Korean cultural content enjoys substantial popularity in Türkiye, this research investigates media coverage patterns of South Korea’s earthquake response. The study employs media analysis methodology using Textom big data analysis software and digital text analysis tools for data collection and word frequency analysis. Both legacy media (39 Turkish newspapers, 143 articles) and new media (36 YouTube videos, 307 text units) were analyzed from February 6 to April 5, 2023. N-gram analysis and textual content analysis identified distinct coverage patterns: legacy media emphasized government-led disaster support, while new media prioritized private sector contributions, particularly donations made by the entertainment industry. The cultural sector emerged as a mediating factor between South Korean and Turkish societies. Word frequency analysis revealed that cultural diplomacy—using culture to positively influence foreign publics— functioned effectively alongside traditional diplomatic efforts. The findings demonstrate that Hallyu amplified South Korea’s disaster assistance effects in Türkiye, confirming its utility as a cultural public diplomacy instrument. The study concludes that diversified Korea-Türkiye collaborative content beyond conventional entertainment could enhance South Korea’s public diplomacy effectiveness. Keywords: public diplomacy, Korean Wave, Hallyu, Korea-Turkey relations, media analysis, disaster response, cultural diplomacy, soft power, digital text analysis